2014
DOI: 10.1530/eje-13-0831
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fetuin-A levels are reduced in patients with hypothyroidism

Abstract: Objective: To determine plasma fetuin-A levels in hypothyroid patients before and after treatment with L-thyroxine (T 4 ) and to determine the relation between plasma fetuin-A levels with cardiovascular risk factors. Design: A prospective, controlled, single-blind study. Methods: Forty-four treatment-naive female patients diagnosed with hypothyroidism and 39 age-and sex-matched control subjects were enrolled. Anthropometric measurements, blood pressure, plasma TSH, fetuin-A, free T 4 , LDL-cholesterol, tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
(45 reference statements)
0
11
1
Order By: Relevance
“…Other authors have found significantly lower plasma fetuin A levels in nondiabetic adult patients with hypothyroidism or Hashimoto thyroiditis [53, 56], but we could not reproduce these findings in our cohort as we did not see a correlation with thyroid-stimulating hormone levels or a clinical diagnosis of thyroiditis. In contrast to some previous reports in non-T1D cohorts, fetuin A levels were not associated with dyslipidemia, any single lipid parameter [8, 9, 14, 55], or microalbuminuria [57].…”
Section: Discussioncontrasting
confidence: 80%
“…Other authors have found significantly lower plasma fetuin A levels in nondiabetic adult patients with hypothyroidism or Hashimoto thyroiditis [53, 56], but we could not reproduce these findings in our cohort as we did not see a correlation with thyroid-stimulating hormone levels or a clinical diagnosis of thyroiditis. In contrast to some previous reports in non-T1D cohorts, fetuin A levels were not associated with dyslipidemia, any single lipid parameter [8, 9, 14, 55], or microalbuminuria [57].…”
Section: Discussioncontrasting
confidence: 80%
“…Selenium is also very promoting as a therapeutic treatment: many studies show that, in autoimmune thyroiditis, the administration of selenium can cause a significant drop in the antibody level (anti‐TPO) . Evaluating the levels of protein markers such as Futuin‐A and CXCL10's may have potential relevance given that they are reported to be increased and decreased in patients, respectively , with a possible diagnostic meaning. Finally, it is significant to consider the variation of FcγRIIB (low‐affinity receptor of IgG) expression on B‐lymphocytes, as the aforementioned autoantibodies exploit the Fcγ receptors in affected patients, given that these receptors are less expressed than in healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the levels of protein markers such as Futuin‐A and CXCL10's may have potential relevance given that they are reported to be increased and decreased in patients, respectively , with a possible diagnostic meaning. Finally, it is significant to consider the variation of FcγRIIB (low‐affinity receptor of IgG) expression on B‐lymphocytes, as the aforementioned autoantibodies exploit the Fcγ receptors in affected patients, given that these receptors are less expressed than in healthy subjects . In addition, HT may represent a challenging disease for pathologists to differentiate from cancer, especially in atypical cytological smears .…”
Section: Discussionmentioning
confidence: 99%
“…HFA is commonly present in the cortical plate of the immature cerebral cortex and the hemopoietic matrix of bone marrow. Low levels of HFA may indicate cardiovascular risks at an early stage (Stefan, 2013) such as in patients on dialysis (Liang et al, 2014), hypothyroidism (Bakiner et al, 2014), and atherosclerosis (Lim et al, 2007). Moreover, increased serum concentrations of HFA may be responsible for cancer cell adhesion and metastasis (Nangami et al, 2013;Sakwe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%